The Russian folktale by Vladimir Yakovlevich Propp - Propp, V. I͡A. (Vladimir I͡Akovlevich), 1895-1970 (Series in fairy-tale studies., 2012)
"[The Russian Folktale is] an impressively wide-ranging work that stimulates through speculation, it provides precisely what the early elaboration of functions declaratively lacks: an etiology of genre, a broad historical perspective, analyses of individual tales, commentary on tale-tellers, engagement with previous scholarship, and examination of a sufficiently broad European context to enable thought-provoking insights into the distinctiveness of Russian folk narratives."--Helena Goscilo -- Book jacket.